TELAAH KRITIS METODE HISAB PENENTUAN AWAL RAMADHAN PENGIKUT HABIB SEUNAGAN NAGAN RAYA-ACEH. - rasyidin rasyidin; ismail ismail (State of Islamic Institute Langsa, 2019)
This journal explains about the Habib Seunagan followers’ calculation method of the beginning of Ramadan’s determination and normative review of the practice of determining the beginning of Ramadan which has been used to date. The result of the research can be explained that Habib Seunagan’s followers use hisab ‘urfi khumasi (not hisab hakiki taqribi) that has been modified from the original method by adding abstinence day before the beginning of Ramadan fasting on Wednesday and Friday to begin Ramadan fasting. Normatively, after considering the legal basis from Alquran, Hadist, and fatwa ulama about the beginning of Ramadan’s determination, then the Habib Seunagan followers’ practice of determining the beginning of Ramadan based on hisab ‘urfi khumasi is not in accordance with the provisions of the law, considering that when starting Ramadan fasting, the essence is still on the 28th or the 29th of Sya’ban based on hisab hakiki tarqibi and can be proven by the sight of the old crescent in the eastern horizon before sunrise on the first day of the Habib Seunagan followers’ Ramadan fasting.